Islamic digital storytelling as a strategy for Islamic education teachers in fostering the religious character of madrasah students - Fajriani Fajriani; Septi Gumiandari (AL-TARBIYAH: Jurnal Pendidikan (The Educational Journal), 2026)
This study analyzes the implementation of Islamic digital storytelling by Islamic Education (PAI) teachers and studies the Islamic values of this medium and their impact on strengthening the religious character of madrasah adolescents in the digital age. The study uses qualitative research with a case study approach involving two PAI teachers and three madrasah students obtained through purposeful sampling . Data were obtained through in-depth interviews, participant observation, documentation, and thematic analysis of 6 stages. This analysis uses digital storytelling narrative theory and the theory of religious character of adolescents. The research analysis shows that the implementation of Islamic digital storytelling covers five main aspects, namely the pedagogical artistic Islamic storytelling narrative design creativity, the pedagogical integration of digital technology and education da'wah, the students' emotional and spiritual resonance, the internalization of digital story Islamic values, and the enhancement of adolescents' religious character in the digital world. The digital storytelling medium demonstrates the capacity to develop madrasah students' affective engagement, moral reflection, and spiritual experience. Therefore, Islamic digital storytelling serves as an important innovative teaching approach combining integrated values, technological and spiritual aspects, and Islamic education.